NILAI MORAL DALAM TRADISI SANTRI PADA NOVEL BIDADARI BERMATA BENING KARYA HABIBURRAHMAN EL SHIRAZY (KAJIAN SOSIOLOGI SASTRA) - Ahmad Ilzamul Hikam; Komariah Bonawati (Jurnal Bastra (Bahasa dan Sastra), 2025)
This research aims to describe illustrations of moral values applied by santri in the novel Bidadari Bermata Berahan by Habiburrahman El Shirazy. In analyzing a literary work, we need an approach as a starting point in its study. One approach used to study this literary work is literary sociology. The reason researchers use a literary sociology approach is because we often apply moral values in dealing with society. Literary sociology is an approach that studies, understands and evaluates literary works from a social or societal perspective.